Tumor Cell Phenotyping: Circulating Tumor Cell Phenotyping via High‐Throughput Acoustic Separation (Small 32/2018). Issue 32 (9th August 2018) - Wu, Mengxi; Huang, Po‐Hsun; Zhang, Rui; Mao, Zhangming; Chen, Chuyi; Kemeny, Gabor; Li, Peng; Lee, Adrian V.; Gyanchandani, Rekha; Armstrong, Andrew J.; Dao, Ming; Suresh, Subra; et al.
Abstract : In article number1801131, Ming Dao, Tony Jun Huang, and co‐workers develop an acoustofluidic device design, which employs an acoustic enclosure and a divider, and enables the isolation of rare circulating tumor cells from peripheral blood in high throughput while preserving their structural, biological, and functional integrity.